Ferrocene functionalized multi-walled carbon nanotubes as supercapacitor electrodes - Ali, Gomaa A. M.; Megiel, Elzbieta; Cieciórski, Piotr; Thalji, Mohammad R.; Romański, Jan; Algarni, H.; K. F., Chong (Elsevier, 2020)
Modified multi-walled carbon nanotubes (MWCNTs) functionalized by a redox-active ferrocene (Fc-MWCNTs) were successfully synthesized to enhance the electrochemical performance of MWCNTs for supercapacitor application. The ferrocene moieties were attached to the surface of MWCNTs via a thiourea linker with anions-interacting capability. The Fc-MWCNTs were characterized using XPS, FTIR, SEM, TGA, DTG, and XRF methods. The electrochemical performance details were investigated using cyclic voltammetry, galvanostatic charge-discharge, and electrochemical impedance spectroscopy. The Fc-MWCNTs electrode showed excellent capacity retention (90.8% over 5000 cycles) and a specific capacitance of 50 F g−1 at 0.25 A g−1 that is several times higher as compared to the pristine MWCNTs. The fabricated Fc-MWCNTs is proposed to be a suitable and promising candidate for energy storage material.